Preparation method of high-purity quartz porous balls

By using electronic grade tetraethoxysilane to prepare high-purity silicic acid precipitates, and through aging, filtration, drying and calcining processes, the high cost and complex problems of the existing quartz porous sphere preparation methods are solved, and the low-cost preparation and industrial production of high-purity quartz porous spheres are achieved.

CN120004280APending Publication Date: 2025-05-16JIANGSU WOHONG EQUIP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510173450.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-05-16

AI Technical Summary

Technical Problem

The existing methods for preparing quartz porous spheres have problems such as high cost, complex process and difficulty in realizing industrialization, and the existing technology is difficult to effectively solve the problem of large-scale production of quartz porous spheres.

Method used

Electronic grade tetraethoxysilane is used as the silicon source, and high-purity silicic acid precipitate is prepared by hydrolysis + polymerization of tetraethoxysilane. After aging, it is filtered, dried and calcined to form high-purity quartz porous spheres.

Benefits of technology

It realizes the preparation of high-purity quartz porous balls at low cost, safe and environmentally friendly, simplifies the process flow, reduces energy consumption, improves the heat and corrosion resistance of the materials, and facilitates industrialization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120004280A_ABST
    Figure CN120004280A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of high-purity quartz porous spheres, which comprises the following steps of: adopting electronic-grade tetraethoxysilane as a silicon source, preparing a high-purity silicic acid precipitate in a tetraethoxysilane hydrolysis and polymerization manner, performing aging treatment to form an aged precipitate, filtering and washing the aged precipitate, and drying and calcining to obtain the high-purity quartz porous spheres. The material is further dehydrated, so that internal organic matters are volatilized to form a cavity, the external quartz surface is partially fused to form a spherical shell, and finally the high-purity quartz porous ball is obtained. The quartz material obtained by the method is spherical and controllable in size, and can be directly used for preparing a structural material instead of a filler. The quartz porous ball is high in purity and has better heat resistance and corrosion resistance. The method has the advantages of simple route, no need of extremely high process temperature, low cost in the production process, low energy consumption, high safety and convenience in realization of industrialization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of inorganic materials, and in particular to a method for preparing a low-cost, safe and environmentally friendly high-purity quartz porous ball. Background Art

[0002] Inorganic porous materials refer to various natural or artificial inorganic non-metallic materials with tiny pores, light weight and large surface area. These materials have the characteristics of large specific surface area, low density, low thermal conductivity and high porosity, and are widely used in catalysts and adsorbents, thermal insulation materials, filter materials, environmental protection, agriculture and other fields. At present, the most commonly used inorganic porous material is white carbon black, which has low strength, large specific surface area and small size, so it can only be used as an additive.

[0003] Quartz material has excellent physical and chemical properties such as high chemical stability, high heat resistance, high insulation, and high mechanical properties. It is a very excellent inorganic material. Quartz is prepared into porous spherical materials, which not only can give full play to the advantages of the quartz material itself, but also because of its internal porous structure, the air contained in the middle of the material can greatly reduce the density of the material, increase the specific surface area of ​​the material, and reduce the insulation and dielectric constant of the material; at the same time, because of its external spherical structure, it can improve the overall fluidity of the material. Its excellent physical and chemical properties can be widely used in many industries such as semiconductors, communications, chemicals, and biomedicine.

[0004] Regarding the preparation method of porous quartz balls, invention patent CN108911487A discloses a porous quartz material and its preparation method, using a high-temperature blowtorch to heat the quartz particles until the surface is melted, and a rotary deposition method is used to deposit to form a loose deposited quartz body. However, this method requires a high heating temperature, high cost, and poor controllability. Invention patent CN106430222A discloses a nano-silica microsphere and its preparation method, using a polymer core as a template and polyalkoxysiloxane as a silicon source, and then removing the polymer core after reaction in an aqueous phase to form a lightweight silica ball. However, this method is complicated to operate, costly, and difficult to industrialize.

[0005] Currently, the large-scale production of synthetic quartz porous balls is still in the exploratory stage. In order to give full play to the advantages of high strength, high specific surface area and high heat resistance of quartz porous materials, it is necessary to develop new quartz porous materials and new preparation methods. Summary of the invention

[0006] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a method for preparing high-purity quartz porous balls, which can prepare high-purity quartz porous balls at low cost, safely and environmentally friendly, and is easy to realize industrialization.

[0007] To achieve the above object, the present invention adopts the following technical solutions:

[0008] The present invention provides a method for preparing a high-purity quartz porous ball, and the method for preparing the high-purity quartz porous ball comprises the following steps:

[0009] Step S1: Mix a silicon source, deionized water and a high-purity catalyst, and stir at a first constant temperature for 1 h to 24 h to obtain a gel-like high-purity silicic acid precipitate; wherein the silicon source is electronic grade tetraethoxysilane, and the high-purity catalyst is high-purity acid or high-purity ammonia water.

[0010] Step S2: mixing the high-purity silicic acid precipitate with electronic-grade ethanol, and aging the mixture at a second constant temperature for 0.5 to 5.0 days to obtain an aged precipitate.

[0011] Step S3: Filter and rinse the aged precipitate with deionized water to clean the ions on the surface of the aged precipitate until the pH value of the filtrate reaches neutral; dry the washed precipitate at a temperature of 120°C to 200°C for 2h to 10h to obtain dry amorphous silicon dioxide.

[0012] Step S4: calcining the amorphous silicon dioxide: placing the amorphous silicon dioxide in a high temperature furnace, heating it to 1000°C to 1300°C at a heating rate of 2°C / min to 10°C / min and keeping it at that temperature for 1h to 30h; after cooling, obtaining a high-purity quartz porous ball.

[0013] Preferably, in step S1, the volume ratio of the silicon source, deionized water and high-purity catalyst is (1-10):(1-6):1.

[0014] Preferably, in step S1, the high-purity acid is electronic-grade hydrochloric acid or electronic-grade nitric acid, the purity of which is not less than 99.99%, and the concentration of which is 0.5 mol / L to 5.0 mol / L.

[0015] Preferably, in step S1, the high-purity ammonia water is electronic-grade ammonia water, the purity of which is not less than 99.99%, and the concentration of which is 0.5 mol / L to 5.0 mol / L.

[0016] Preferably, in step S1, the first constant temperature is 50°C to 90°C.

[0017] Preferably, in step S2, the second constant temperature is 50°C to 80°C.

[0018] Preferably, in step S1 and step S3, the resistivity of the deionized water is greater than 16.5 MΩ·cm, and the total organic carbon is less than 20 ppmw.

[0019] Preferably, the diameter of the high-purity quartz porous sphere obtained in step S4 is 0.1 mm to 10 mm.

[0020] Preferably, the purity of the high-purity quartz porous spheres obtained in step S4 is 5N to 6N.

[0021] Preferably, the high-purity quartz porous sphere obtained in step S4 is rich in micropores, and the pore size of the micropores is 10 μm to 200 μm.

[0022] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention uses electronic grade tetraethoxysilane as a silicon source, and utilizes the hydrolysis + polymerization of tetraethoxysilane to prepare a high-purity silicic acid precipitate, and after aging treatment, an aged precipitate is formed, and then the aged precipitate is filtered and rinsed, and then the material is further dehydrated by drying and calcining, so that the internal organic matter is volatilized to form a cavity, and the external quartz surface is partially melted to form a spherical shell, and finally a high-purity quartz porous ball is obtained. The quartz material obtained by this method is spherical, and the size is controllable, and can be directly used to prepare structural materials instead of fillers. The purity of the quartz porous ball is very high, and it has better heat resistance and corrosion resistance. This method has a simple route, does not require extremely high process temperature, has low production cost, low energy consumption, and high safety, and is easy to realize industrialization. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The present invention is a flow chart of a method for preparing a high-purity quartz porous ball.

[0024] Figure 2 This is a cross-sectional SEM (Scanning Electron Microscope) photograph of a high-purity quartz porous ball prepared by the present invention. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described below in conjunction with the accompanying drawings of the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention. It can be understood that some technical means of the various embodiments described herein can be replaced or combined with each other without conflict.

[0026] In the description of the present invention, if there are terms such as "first", "second", etc., they are only used to distinguish the objects described, and do not have any order or technical meaning. Therefore, the objects defined as "first", "second", etc. may explicitly or implicitly include one or more of the objects. In addition, "one" or "a" and similar words do not indicate a quantity limitation, but indicate the existence of at least one, and "multiple" means not less than two.

[0027] In the description of the present specification, reference to "one embodiment" or "some embodiments" etc. means that one or more embodiments of the present invention include a specific feature, structure or characteristic described in conjunction with the embodiment. Therefore, the phrases "in one embodiment", "in some embodiments", "in some other embodiments", "in some other embodiments", etc. appearing in different places in this specification do not necessarily refer to the same embodiment, but mean "one or more but not all embodiments", unless otherwise specifically emphasized in other ways.

[0028] The present invention provides a method for preparing high-purity quartz porous balls, which can prepare high-purity quartz porous balls at low cost, safely and environmentally friendly, and is easy to realize industrialization.

[0029] Reference Figure 1 The preparation method of the high-purity quartz porous ball comprises the following steps:

[0030] Step S1: Mix a silicon source, deionized water and a high-purity catalyst, and stir at a first constant temperature for 1 hour to 24 hours to obtain a gel-like high-purity silicic acid precipitate. The silicon source is electronic grade tetraethoxysilane (TEOS, TetraethylOrthosilicate), and the high-purity catalyst is a high-purity acid or high-purity ammonia water (NH3·H2O).

[0031] Tetraethoxysilane (TEOS), also known as tetraethyl silicate or ethyl orthosilicate, is an organic compound with the chemical formula C8H 20 O4Si or Si(OCH2CH3)4 is a colorless liquid, slightly soluble in water, slightly soluble in benzene, soluble in ether, and miscible in ethanol. The above steps mainly utilize the hydrolysis + polymerization of tetraethoxysilane to prepare high-purity silicic acid precipitate. The high-purity catalyst is used to provide acidic or alkaline conditions to promote the hydrolysis reaction.

[0032] Specifically, the process of preparing high-purity silicic acid precipitate by hydrolysis and polymerization of tetraethoxysilane includes:

[0033] (1) Tetraethoxysilane undergoes hydrolysis reaction in acidic or alkaline environment:

[0034]

[0035] (2) Dehydration condensation reaction:

[0036] Si(OH)4+Si(OH)4——→(OH)3Si-O-Si(OH)3+H2O

[0037] (3) Dealcoholization condensation reaction:

[0038] Si(OH)4+Si(OC2H5)4——→(OH)3Si-O-Si(OC2H5)3+C2H5OH

[0039] (4) Polymerization reaction:

[0040] n(Si-O-Si)——→(-Si-O-Si-) n

[0041] In some embodiments, the high-purity acid may be electronic-grade hydrochloric acid (HCL) or electronic-grade nitric acid (HNO3), the purity of which is not less than 99.99%, and the concentration thereof is 0.5 mol / L (mole / liter) to 5.0 mol / L. The high-purity ammonia water may be electronic-grade ammonia water, the purity of which is not less than 99.99%, and the concentration thereof is 0.5 mol / L to 5.0 mol / L. The resistivity of the deionized water is greater than 16.5 MΩ·cm (megaohm·cm), and the total organic carbon is less than 20 ppmw. The optional range of the first constant temperature is 50°C to 90°C.

[0042] Furthermore, the volume ratio of silicon source, deionized water and high-purity catalyst is (1-10):(1-6):1.

[0043] Step S2: Mix the high-purity silicic acid precipitate with electronic-grade ethanol, and age the mixture at a second constant temperature for 0.5 to 5.0 days to obtain an aged precipitate. The electronic-grade ethanol has a purity of not less than 99.99%, a concentration of 0.5 mol / L to 5.0 mol / L, and a volume ratio of the high-purity silicic acid precipitate to the electronic-grade ethanol is (1 to 10): (1 to 100).

[0044] In some embodiments, the second constant temperature may range from 50°C to 80°C.

[0045] Step S3: Filter and rinse the aged precipitate with deionized water to clean the ions on the surface of the aged precipitate until the pH value of the filtrate reaches neutral, that is, the pH value of the filtrate reaches 7; dry the washed precipitate at a temperature of 120°C to 200°C for 2 hours to 10 hours to obtain dry amorphous silicon dioxide. The resistivity of the deionized water is greater than 16.5MΩ·cm, and the total organic carbon is less than 20ppmw.

[0046] Step S4: calcining amorphous silicon dioxide: placing amorphous silicon dioxide in a high-temperature furnace, heating to 1000°C to 1300°C at a heating rate of 2°C / min (degrees Celsius / minute) to 10°C / min and keeping the temperature for 1h (hour) to 30h; after cooling, obtaining a high-purity quartz porous sphere.

[0047] The present invention adopts electronic grade tetraethoxysilane as silicon source, and prepares high-purity silicic acid precipitation by hydrolysis + polymerization of tetraethoxysilane. After aging treatment, an aged precipitate is formed. After that, the aged precipitate is filtered and rinsed, and then the material is further dehydrated by drying and calcining, so that the internal organic matter is volatilized to form a cavity, and the external quartz surface is partially melted to form a spherical shell, and finally a high-purity quartz porous ball is obtained. This method has a simple route, does not require extremely high process temperature, has low production cost, low energy consumption, high safety, and is easy to realize industrialization. Using the above method, high-purity quartz porous balls can be synthesized at low cost, safely and environmentally friendly, and the surface is smooth spherical, which can improve the fluidity of the whole material, and the diameter is 0.1mm (millimeter) ~ 10mm, and the size is controllable, and can be directly used to prepare structural materials instead of fillers. The purity of the high-purity quartz porous ball is very high, the purity can reach 5N ~ 6N level, and has better heat resistance and corrosion resistance. It should be noted that the N in the purity level here is the abbreviation of "nine" in English, which means the number of "9" in the purity level. For example, 3N means the purity is 99.9%, 4N means the purity is 99.99%, and so on.

[0048] Referring to Table 1 below, in one embodiment, the impurity elements in the prepared high-purity quartz porous spheres were detected, and the total content of the impurity elements in the high-purity quartz porous spheres was measured to be 4.6 ppmw, and the purity of the high-purity quartz porous spheres reached 5N5 level.

[0049] Table 1 Impurity content test results of high purity quartz porous balls

[0050] Impurities Li Na K Al Fe Ti Ca Content (ppmw) ~ 0.9 0.6 0.1 0.5 0.1 2.0 Impurities Mg Cr Ni Mn Cu B total Content (ppmw) ~ ~ ~ ~ ~ 0.4 4.6

[0051] Among them, “~” indicates that the content of the element is lower than the detection limit.

[0052] In addition, refer to Figure 2 The cross-sectional SEM (Scanning Electron Microscope) photograph of the high-purity quartz porous sphere shown in the figure shows that the interior of the high-purity quartz porous sphere is rich in micropores with a pore size of 10 μm (micrometer) to 200 μm, which can greatly reduce the density of the material, increase the specific surface area of ​​the material, and reduce the insulation and dielectric constant of the system.

[0053] Three embodiments of the present invention are given below.

[0054] Embodiment 1:

[0055] The preparation method of high-purity quartz porous ball comprises the following steps:

[0056] Step S1: electronic grade tetraethoxysilane, deionized water and electronic grade ammonia water with a concentration of 2.0 mol / L are mixed in a volume ratio of 4:4:1, and stirred at a first constant temperature of 80° C. for 2 h to obtain a gel-like high-purity silicic acid precipitate.

[0057] Step S2: Mix the high-purity silicic acid precipitate with electronic-grade ethanol, and age it at a second constant temperature of 70° C. The aging time is 1.0 day to obtain an aged precipitate.

[0058] Step S3: Filter and rinse the aged precipitate with deionized water to clean the ions on the surface of the aged precipitate until the pH value of the filtrate reaches neutral; place the washed precipitate filter cake on a heating plate at 150° C. for drying and dehydration for 3 hours to obtain dry amorphous silicon dioxide.

[0059] Step S4: calcining the amorphous silicon dioxide: placing the amorphous silicon dioxide in a high-purity quartz crucible, placing the high-purity quartz crucible in a muffle furnace, heating to 1100° C. at a heating rate of 10° C. / min and keeping the temperature for 8 hours; after cooling, obtaining a high-purity quartz porous ball.

[0060] After testing, the diameter of the high-purity quartz porous ball prepared by the method of Example 1 is 0.1mm-1.0mm, the total impurity content is 9.8ppmw, the purity reaches 5N level, and the micropore diameter inside is 10μm (micrometer)-50μm.

[0061] Embodiment 2:

[0062] The preparation method of high-purity quartz porous ball comprises the following steps:

[0063] Step S1: electronic grade tetraethoxysilane, deionized water and electronic grade hydrochloric acid with a concentration of 1.0 mol / L are mixed in a volume ratio of 2:1:1, and stirred at a first constant temperature of 60° C. for 4 hours to obtain a gel-like high-purity silicic acid precipitate.

[0064] Step S2: mixing the high-purity silicic acid precipitate with electronic-grade ethanol, and aging the mixture at a second constant temperature of 60° C. for 3.0 days to obtain an aged precipitate.

[0065] Step S3: Filter and rinse the aged precipitate with deionized water to clean the ions on the surface of the aged precipitate until the pH value of the filtrate reaches neutral; place the washed precipitate filter cake on a heating plate at 170° C. for drying and dehydration for 4 hours to obtain dry amorphous silicon dioxide.

[0066] Step S4: calcining amorphous silicon dioxide: placing amorphous silicon dioxide in a high-purity quartz crucible, placing the high-purity quartz crucible in a muffle furnace, heating to 1150° C. at a heating rate of 5° C. / min and keeping the temperature for 6 hours; after cooling, obtaining a high-purity quartz porous ball.

[0067] After testing, the diameter of the high-purity quartz porous ball prepared by the method of Example 2 is 0.5mm-5.0mm, the total impurity content is 4.4ppmw, the purity reaches 5N5 level, and the micropore diameter inside is 10μm (micrometer)-100μm.

[0068] Embodiment 3:

[0069] The preparation method of high-purity quartz porous ball comprises the following steps:

[0070] Step S1: electronic grade tetraethoxysilane, deionized water and electronic grade nitric acid with a concentration of 5.0 mol / L are mixed in a volume ratio of 10:5:1, and stirred at a first constant temperature of 50° C. for 10 hours to obtain a gel-like high-purity silicic acid precipitate.

[0071] Step S2: mixing the high-purity silicic acid precipitate with electronic-grade ethanol, and aging the mixture at a second constant temperature of 70° C. for 5.0 days to obtain an aged precipitate.

[0072] Step S3: Filter and rinse the aged precipitate with deionized water to clean the ions on the surface of the aged precipitate until the pH value of the filtrate reaches neutral; place the washed precipitate filter cake on a heating plate at 140° C. for drying and dehydration for 6 hours to obtain dry amorphous silicon dioxide.

[0073] Step S4: calcining amorphous silicon dioxide: placing amorphous silicon dioxide in a high-purity quartz crucible, placing the high-purity quartz crucible in a muffle furnace, heating to 1250° C. at a heating rate of 3° C. / min and keeping the temperature for 4 hours; after cooling, obtaining a high-purity quartz porous ball.

[0074] After testing, the diameter of the high-purity quartz porous ball prepared by the method of Example 3 is 1.0 mm to 7.5 mm, the total impurity content is 2.7 ppmw, the purity reaches 5N7 level, and the micropore diameter inside is 10 μm (micrometer) to 200 μm.

[0075] The present invention adopts electronic grade tetraethoxysilane as silicon source, and prepares high-purity silicic acid precipitation by hydrolysis + polymerization of tetraethoxysilane. After aging treatment, an aged precipitate is formed. After that, the aged precipitate is filtered and rinsed, and then the material is further dehydrated by drying and calcining, so that the internal organic matter is volatilized to form a cavity, and the external quartz surface is partially melted to form a spherical shell, and finally a high-purity quartz porous ball is obtained. The quartz material obtained by this method is spherical, and the size is controllable, and can be directly used to prepare structural materials instead of fillers. The purity of the quartz porous ball is very high, and it has better heat resistance and corrosion resistance. This method has a simple route, does not require extremely high process temperature, has low production process cost, low energy consumption, and high safety, and is easy to realize the industrialization of the quartz material preparation process.

[0076] The present invention has been described by the above-mentioned relevant embodiments, however, the above-mentioned embodiments are only examples for implementing the present invention. It must be pointed out that the disclosed embodiments do not limit the scope of the present invention. On the contrary, changes and modifications made without departing from the spirit and scope of the present invention are all within the scope of patent protection of the present invention.

Claims

1. A method for preparing high-purity quartz porous balls, characterized in that: The preparation method of the high-purity quartz porous ball comprises the following steps: Step S1: mixing a silicon source, deionized water and a high-purity catalyst, and stirring at a first constant temperature for 1 h to 24 h to obtain a gel-like high-purity silicic acid precipitate; wherein the silicon source is electronic grade tetraethoxysilane, and the high-purity catalyst is high-purity acid or high-purity ammonia water; Step S2: mixing the high-purity silicic acid precipitate with electronic-grade ethanol, and aging the mixture at a second constant temperature for 0.5 to 5.0 days to obtain an aged precipitate; Step S3: filtering and washing the aged precipitate with deionized water to clean the ions on the surface of the aged precipitate until the pH value of the filtrate reaches neutral; drying the washed precipitate at a temperature of 120° C. to 200° C. for 2 h to 10 h to obtain dry amorphous silicon dioxide; Step S4: calcining the amorphous silicon dioxide: placing the amorphous silicon dioxide in a high temperature furnace, heating it to 1000°C to 1300°C at a heating rate of 2°C / min to 10°C / min and keeping it at that temperature for 1h to 30h; after cooling, obtaining a high-purity quartz porous ball.

2. The method for preparing high-purity quartz porous balls according to claim 1, characterized in that: In step S1, the volume ratio of silicon source, deionized water and high-purity catalyst is (1-10):(1-6):

1.

3. The method for preparing high-purity quartz porous balls according to claim 1, characterized in that: In step S1, the high-purity acid is electronic grade hydrochloric acid or electronic grade nitric acid, the purity of which is not less than 99.99%, and the concentration of which is 0.5 mol / L to 5.0 mol / L.

4. The method for preparing a high-purity quartz porous ball according to claim 1, characterized in that: In step S1, the high-purity ammonia water is electronic grade ammonia water, the purity of which is not less than 99.99%, and the concentration of which is 0.5 mol / L to 5.0 mol / L.

5. The method for preparing high-purity quartz porous balls according to claim 1, characterized in that: In step S1, the first constant temperature is 50°C to 90°C.

6. The method for preparing a high-purity quartz porous ball according to claim 1, characterized in that: In step S2, the second constant temperature is 50°C to 80°C.

7. The method for preparing high-purity quartz porous balls according to claim 1, characterized in that: In step S1 and step S3, the resistivity of the deionized water is greater than 16.5 MΩ·cm, and the total organic carbon is less than 20 ppmw.

8. The method for preparing high-purity quartz porous balls according to claim 1, characterized in that: The diameter of the high-purity quartz porous sphere obtained in step S4 is 0.1 mm to 10 mm.

9. The method for preparing a high-purity quartz porous ball according to claim 1, characterized in that: The purity of the high-purity quartz porous spheres obtained in step S4 is 5N to 6N.

10. The method for preparing high-purity quartz porous balls according to claim 1, characterized in that: The high-purity quartz porous ball obtained in step S4 is rich in micropores, and the pore size of the micropores is 10 μm to 200 μm.

Citation Information

Patent Citations

  • Nanosilicon dioxide pellet and preparing method thereof

    CN106430222A

  • Porous quartz material and preparation method thereof

    CN108911487A